Association between body mass index and risk of total knee replacement, the Singapore Chinese Health Study. Issue 1 (January 2015) - Leung, Y.-Y.; Allen, J.C.; Noviani, M.; Ang, L.-W.; Wang, R.; Yuan, J.-M.; Koh, W.-P.
Summary: Purpose: Data on the association between body mass index (BMI) and risk of knee osteoarthritis (KOA) are sparse for Asian populations who are leaner than Western populations. We evaluated the association between BMI and risk of total knee replacement (TKR) due to severe KOA among Chinese in Singapore. Methods: We used data from the Singapore Chinese Health Study (SCHS), a population-based prospective cohort of 63, 257 Chinese men and women, aged 45–74 years at enrollment from 1993 to 1998. Information on height, weight, diet and lifestyle factors were obtained via in-person interviews. TKR cases for severe KOA were identified via linkage with the nationwide hospital discharge database through 2011. Cox regression and weighted least squares regression were used in the analysis. Results: The mean BMI among cohort participants was 23.1 kg/m 2, and more than two-thirds had BMI below 25 kg/m 2 . A total of 1649 had TKR attributable to severe KOA. Risk of TKR increased in a strong dose-dependent manner with increasing BMI throughout the 15–32 kg/m 2 range and became less clear at BMI >32 kg/m 2 . In the BMI range 16–27 kg/m 2, there was a 27% increase in TKR risk for each unit increase in BMI ( P for trend < 0.001). Compared to BMI 19–20 kg/m 2, the risk estimates of TKR were all statistically significant with increasing unit of BMI ≥21 kg/m 2 . Results were similar for men and women. Conclusion: Our results provided evidence for a constant mechanical mechanism underlying BMI and KOA initiation and/or progression.